From Annulment to Recognition: State Power, Historical Revisionism and the Politics of Memory in Nigeria’s Democracy Day (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
Nigeria’s democratic journey began in the 1960s after independence from Britain but recorded setbacks arising from military coups that paved the way for transition to civil rule. This paper critically explores how June 12, which was once an annulment of elections day and national trauma in 1993, was declared as Nigeria’s Democracy Day in 2018 by way of formal proclamation. It examines how Nigerian governments, one after another, have engaged in historical revisionism to reshape people’s memory and political legitimacy through selective narratives of the past. Drawing from secondary sources, media and policy reports, and academic critiques, the study problematizes the convergence of state power, national identity-making and memory politics. It dwells on how symbolic rehabilitation of June 12 and posthumous commemoration of Chief M. K. O. Abiola form a gesture of atonement and instrumental effort by the state to renegotiate its democratic heritage. The paper argues that, although the official holiday on 12th June is a significant step towards democracy in Nigeria, it also reveals underlying tensions between popular historical consciousness and official memory. The study calls for a more inclusive and dialogical memorialization beyond political opportunism and actual national reconciliation.